2014
DOI: 10.1038/srep06549
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured organosilicon luminophores and their application in highly efficient plastic scintillators

Abstract: Organic luminophores are widely used in various optoelectronic devices, which serve for photonics, nuclear and particle physics, quantum electronics, medical diagnostics and many other fields of science and technology. Improving their spectral-luminescent characteristics for particular technical requirements of the devices is a challenging task. Here we show a new concept to universal solution of this problem by creation of nanostructured organosilicon luminophores (NOLs), which are a particular type of dendri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 51 publications
0
29
0
Order By: Relevance
“…4. Earlier investigation of the optical properties of the organosilicon dendritic molecular antennas have shown that photons in these systems are absorbed by the donor and acceptor chromophores independently of each other and there is no π-conjugation between the chromophores linked through silicon atoms in the molecules [29,30,32]. Therefore, it is not surprising that comparison of the absorption spectra of NOL4 and NOL5 with the corresponding model compounds 1 and 2 indicated that the absorption spectra of these dendritic molecules is a sum of the absorption spectra of the bithiophenesilane (2T) and 1,4-bis(2,2'-bithiophene-5-yl)benzene (2T-Ph-2T) fragments (Fig.…”
Section: Optical Properties In Dilute Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…4. Earlier investigation of the optical properties of the organosilicon dendritic molecular antennas have shown that photons in these systems are absorbed by the donor and acceptor chromophores independently of each other and there is no π-conjugation between the chromophores linked through silicon atoms in the molecules [29,30,32]. Therefore, it is not surprising that comparison of the absorption spectra of NOL4 and NOL5 with the corresponding model compounds 1 and 2 indicated that the absorption spectra of these dendritic molecules is a sum of the absorption spectra of the bithiophenesilane (2T) and 1,4-bis(2,2'-bithiophene-5-yl)benzene (2T-Ph-2T) fragments (Fig.…”
Section: Optical Properties In Dilute Solutionsmentioning
confidence: 99%
“…Solution of this problem has been demonstrated recently by the utilization of oligothiophenephenylene or oligophenylene chromophores having higher luminescence efficiency as compared to oligothiophenes [32,33]. These novel highly luminescent branched molecules were named as "nanostructured organosilicon luminophores" (NOLs) due to the interesting observation that their optical properties combine the best characteristics of organic luminophores and inorganic quantum dots [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is also necessary to take into account optical losses (L) related to self-absorption of a particular luminophore because of partial overlap of its absorption and luminescence spectra, a measure of which can be related to the difference between their maxima called as the Stokes shift (S). To solve these problems, we recently suggested the concept of "Nanostructured Organosilicon Luminophores" (NOLs) [17,18], which are a kind of highly efficient dendritic molecular antenna [19,20], consisting of donor and acceptor fragments covalently linked through silicon atoms with very efficient Förster resonance energy transfer (FRET) between them.…”
Section: Introductionmentioning
confidence: 99%
“…4 , (PTPTP)Si 2 (2T-Hex) 6 and (PTPTP)Si 6 (2T) 4 (2T-Hex) 8 synthesized and investigated in this work. [17], (2,2'-bithien-5-yl)[bis(5'-hexyl-2,2'-bithien-5-yl)]methylsilane 2T-SiMe(2T-Hex) 2 [19] were prepared as reported before. Synthesis of 1,4-bis[5-{4-(trimethylsilyl)phenyl}thiophene-2-yl]benzene (TMS-PTPTP-TMS) and 1,4-bis[5-{4-[tris(5'-hexyl-2,2'-bithien-5-yl)silyl]phenyl}thiophene-2-yl]benzene (PTPTP)Si 2 (2T-Hex) 6 was described elsewhere [26].…”
Section: Introductionmentioning
confidence: 99%